Diseño e implementación de una red de equipamientos colectivos en el polígono MI en la zona sur de Riobamba - Paredes Paredes, Yesenia Estefanía (2022)
An industrial park is understood to be the geographically delimited surfaces designed for the development of industrial settlements, considered essential pieces in a city since they directly help the economic and social growth of the city. In Riobamba, the industrial park is a piece that has been neglected, causing urban voids, buildings in disrepair, and abandoned structures; however, it is an important piece in the morphological and economic development of the city. In the following work, the current state of the Riobamba industrial park, specifically the low-impact polygon, is evaluated through a macro and micro diagnosis, which allowed defining the problems and needs of the sector in order to identify infrastructures that can be intervened and be reused to propose new facilities in the area that enhance the lifestyle of that place, all from a theoretical basis and through the analysis of references to better understand how these facilities are related to the city. In this way, a network of facilities was defined that, together with a master plan, would allow this industrial estate to integrate with the city and stop being a separate entity from it, which combined with a series of guidelines and strategies based on the diagnosis allow you to visualize this proposal in a concise way